2003
DOI: 10.1016/s0166-3615(03)00034-4
|View full text |Cite
|
Sign up to set email alerts
|

A planning and management infrastructure for large, complex, distributed projects—beyond ERP and SCM

Abstract: Enterprises which are distributed in space and/or which are composed as a temporary joint venture of legally different units recently often called virtual (extended) enterprises. Planning, design and operation (management) goals and requirements of such firms are generally different from those of single, centralized enterprises. The basic feature of an extended (virtual) enterprise is that the co-operating units of it keep their independence during the life-cycle of the co-operation-what is well regulated by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(25 citation statements)
references
References 2 publications
0
22
0
3
Order By: Relevance
“…The management of these processes requires close collaboration between different parties in a supply chain (SC), e.g., raw materials suppliers, manufacturers, distributors, and retailers, to attain the ultimate goal of satisfying customer requirements and reducing costs.To ensure that items are delivered on time and to the right place at a low cost, it is most desirable to use information technology (IT) to trace and track the status of the item flows and support the associated information interchange in a supply chain [4,9]. Before embarking on any IT initiatives for SCM, it is important to consider the diffusion, market acceptance, and legitimacy of IT in SCs to facilitate and support trading and communication among the supply chain partners to ensure its effective implementation.…”
mentioning
confidence: 99%
“…The management of these processes requires close collaboration between different parties in a supply chain (SC), e.g., raw materials suppliers, manufacturers, distributors, and retailers, to attain the ultimate goal of satisfying customer requirements and reducing costs.To ensure that items are delivered on time and to the right place at a low cost, it is most desirable to use information technology (IT) to trace and track the status of the item flows and support the associated information interchange in a supply chain [4,9]. Before embarking on any IT initiatives for SCM, it is important to consider the diffusion, market acceptance, and legitimacy of IT in SCs to facilitate and support trading and communication among the supply chain partners to ensure its effective implementation.…”
mentioning
confidence: 99%
“…Without earlier experience from similar projects, the managers and controllers of a project cannot anticipate when and where project cost overruns are likely to occur. Those challenges were also recognized by Kovács and Paganelli (2003), who stated that the activities of complex projects are usually geographically distributed and activities are performed in unprepared or even hostile environments. Those "unprepared or hostile environments" in combination with the technically large scope create challenges for commissioning -which was also recognized as www.ccsenet.org/ijbm International Journal of Business and Management Vol.…”
Section: Discussionmentioning
confidence: 99%
“…A complex and distributed project organization increases the complexity of the cost structure, which causes challenges in detecting potential or actual cost overruns (Kovács & Paganelli, 2003). Intra-organizational transactions also required more delicate margin calculation and a wider cost control.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature has identified the need for many ICT systems, procedures and standards to be implemented within a virtual enterprise in order to increase the effectiveness of collaboration. The main emphasis of the research lies with the interoperability between platforms, that is: ensuring that companies using different internal systems for their design and other business operations can exchange data seamlessly between the two [17], [18].…”
Section: 3inter-operabilitymentioning
confidence: 99%